Analisis Pengaruh Abu Tempurung Kelapa terhadap Kuat Tekan Beton Memadat Sendiri (Self Compacting Concrete) - Chelvia, Chyndi; Purwandito, Meilandy; Irwansyah, Irwansyah (Jurnal Komposit: Jurnal Ilmu-ilmu Teknik Sipil, 2024)
Research in the concrete industry aims to improve the quality of concrete using advanced technology and techniques. One of the innovations carried out is the use of additional materials in SCC concrete, namely coconut shell ash. This research uses coconut shell ash as an additional material with the proportion of coconut shell ash used being 0%, 5%, 15% and 25% of the cement weight with a maximum aggregate accuracy of 20 mm. The reference used in making the concrete mix is the EFNARC Mix Design with a design compressive strength (f'c) of 20 MPa. The test object is cylindrical with a diameter of 15 cm and a height of 30 cm. The tests carried out were compression tests with treatment for 14 and 28 days. The results of adding coconut shell ash to SCC concrete have an influence on the workability characteristics of concrete in the form of a maximum slump flow value in the SCC0 concrete variation without additional coconut shell ash of 650 mm and a minimum slump flow value found in the unmixed concrete (BN) variation of 330 mm and The results of the v-funnel test experienced a decrease in flow time as the coconut shell ash increased, this was caused by the higher the percentage of coconut shell ash used, the thicker the concrete properties would be. The results of the comparison value of unmixed concrete (BN) and SCC concrete with variations in the addition of coconut shell ash to the compressive strength of concrete at the ages of 14 and 28 days showed a decrease in the compressive strength value of concrete along with increasing the percentage of coconut shell ash used. The highest decrease in the compressive strength value of unmixed concrete (BN) occurred in the SCCA25 variation, 55.50% at 14 days and 61.06% at 28 days.